Glucose levels, diabetes duration, vitamin intake and their association with cognitive function in patients with type 2 diabetes mellitus - Khairizka Citra Palupi; Siti Irma Durotunisa; Rachmanida Nuzrina; Yulia Wahyuni; Harna Harna (AcTion: Aceh Nutrition Journal, 2025)
Type 2 Diabetes Mellitus may also contribute to cognitive decline.  Risk factors for cognitive decline in patients with type 2 DM include demographic characteristics, clinical conditions, and nutritional intake. However, there is controversy regarding whether micronutrient intake affects cognitive function among type 2 DM. Thus, we aimed to investigate the determinants of cognitive function in patients with type 2 diabetes mellitus. A cross-sectional design was used in this study. This research was conducted in Marzoeki Mahdi Hospital, Bogor, West Java, from May to June 2023 among 98 respondents. Data on blood glucose levels (HbA1c) were obtained from medical records over the last three months. Nutritional intake was assessed using the SQ-FFQ and cognitive function was assessed using the MoCA-Ina. A significant relationship was found between blood glucose levels, age, illness duration, and cognitive function (r=-0,212, p=0,036; r=-0,736, p=0,0001; r=-0,573, p=0,0001). However, there was no significant relationship between vitamin B12 or C intake and global cognitive function (r=-0,005; p=0,959, r=0,126; p=0,217). There was a relationship between vitamin C and aspects of cognitive function, namely, abstraction (r=0,350, p=0,0001). In conclusion, there is a relationship between blood glucose levels, age, and duration of DM and cognitive function. Vitamin C consumption is associated with abstraction ability.